The Effect of Employee Safety Training Frequency and Compliance on the Reducement of Workplace Accidents at Dr. Nur Clinic in Cimahi City - Natauli Margareta; A. Rohendi; Mochamad Sukrisno Mardiyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Workplace accidents in healthcare facilities are an important issue that has a significant impact on the safety of medical personnel, organizational efficiency, and service quality. Based on data showing an increase in workplace accident cases in Indonesia, a systematic approach is needed, including occupational safety and health (OSH) training and improving OSH compliance. This study aims to analyze the influence of the number of training sessions and compliance with workplace safety on the number of workplace accidents at Dr. Nur Clinic in Cimahi. The study employs a quantitative cross-sectional design with total sampling of all staff members (n=139). Primary data were collected through a questionnaire regarding the frequency of training, compliance with K3, and the number of workplace accidents over the past two years. Data were analyzed using multiple linear regression analysis. The results showed that the frequency of OSH training had a significant negative effect on the number of workplace accidents (r = -0.218; p = 0.028), with R² = 0.048, indicating that 4.8% of the variation in workplace accident incidents was explained by the frequency of training. Meanwhile, compliance with workplace safety showed a stronger and more significant negative correlation (r = -0.307; p = 0.002), with R² = 0.095, indicating a 9.5% contribution to reducing workplace accidents. Multiple regression analysis shows that both variables simultaneously influence the reduction in workplace accidents with an R² of 0.211 (p < 0.001), meaning that 21.1% of the variation in workplace accident incidents can be explained by the combination of both variables. These findings suggest that although the impact of each variable is moderate, the integration of training and improved compliance is more effective in creating a safer work environment. This study can serve as a basis for the development of more comprehensive OSH policies and learning for other health services in creating a strong safety culture.